Improved design of polymeric composite electrothermal micro-actuator for high track density hard disk drives - Yang, J. P. (2014)
Recently, we have developed a polymeric composite electrothermal micro-actuator for dual-stage applications in hard disk drives (HDDs). The polymer composite was demonstrated with a larger thermal expansion as compared to silicon. Yet, the previous design of polymeric composite thermal actuator was stiff, having a high mechanical resonant frequency at 33 kHz and a moderate static displacement stroke of 50 nm at 4 V. An even larger stroke above 100 nm is generally required to meet the need of HDD dual-stage systems. To meet the requirement for a large stroke, we presented an improved design of polymeric composite electrothermal micro-actuator by increasing flexibility of the composite thermal benders. As compared to the previous design, the new design doubled the displacement stroke up to 106 nm at 4 V while it maintained a high mechanical resonant frequency of 31 kHz, slightly below that of the previous design. In addition, a finite element analysis showed that electrothermal activation of the micro-actuator is rather localized and it causes only a small temperature rise of the neighbouring parts of head gimbal assembly. These good performances suggested that this improved design of thermal micro-actuator is promising for high bandwidth dual-stage positioning systems in future high track density HDDs.